Double beam backward wave oscillator on the spiral folded rectangular waveguide - A. A. Kurayev; V. V. Matveyenko; A. O. Rak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A new design of the backward wave oscillator (BWO) terahertz range with two wide tape electronic beam is proposed. As the electrodynamic structure BWO proposed to use spiral folded waveguide on fundamental mode H10. In contrast to existing designs BWO on the wavy folded waveguide [1] proposed BWO has two advantages: 1) tape electron beam may have a width ( - wavelength in the waveguide), whereas in the BWO on wavy folded waveguide because opposite direction of wave propagation in the waveguide adjacent sections. This opens the opportunity to significantly increase the current electron optics and thus significantly improve the output characteristics of the BWO; 2) when the electron beams excite only the backward wave, the forward wave is absent, in contrast to the BWO on wavy folded waveguides, where the narrow electron beam is equally exciting backward and forward waves.